A pilot study of client’s changes instrument in self-perception, perception towards others, personality and behaviour - Zainudin, Zaida Nor; Ahmad, Nor Aniza; Hassan, Siti Aishah; Asri, Alia Sarah (Malaysian Association of Research and Education for Educators, 2020)
A successful counselling session are usually measured either based on the academic changes or behaviour changes of the clients. But, there is the need to see what are the changes take place in clients’ mind or called ‘insight’. To measure the insight of the clients, the researcher developed instrument called Client’s Changes Instrument. Client’s Changes Instrument is constructed based Carl Rogers' book, “Client-Centered Therapy” that outlined the client changes after counselling sessions. The instrument has 4 constructs that are Changes in Self-Perception, Changes in Perception towards Others, Changes in Personality and Changes in Behaviour. The instruments is administered to 32 participants of secondary school students aged 13 to 16 in a selected Malaysia secondary school. Cronbach alpha is used in determining the reliability if the instrument. The result shows that this instrument has high reliability as the value of Cronbach alpha is α=.957. The reliability of each construct also indicated high reliability as Changes in Self-Perception (α= .928), Changes in Perception towards Others (α=.847), Changes in Personality (α= .839) and Changes in Behaviour (α= .850). With the outcome of this instrument, it is an instrument with high reliability and can be used by counsellors to check their effectiveness in their services.